Direct interaction of Na-azide with the KATP channel. - Trapp, S; Ashcroft, F (2000)
1. The effects of the metabolic inhibitor sodium azide were tested on excised macropatches from Xenopus oocytes expressing cloned ATP-sensitive potassium (KATP) channels of the Kir6.2/SUR1 type. 2. In inside-out patches from oocytes expressing Kir6.2 delta C36 (a truncated form of Kir6.2 that expresses in the absence of SUR), intracellular Na-azide inhibited macroscopic currents with an IC50 of 11 mM. The inhibitory effect of Na-azide was mimicked by the same concentration of NaCl, but not by sucrose. 3. Na-azide and NaCl blocked Kir6.2/SUR1 currents with IC50 of 36 mM and 19 mM, respectively. Inhibition was abolished in the absence of intracellular Mg2+. In contrast, Kir6.2 delta C36 currents were inhibited by Na-azide both in the presence or absence of intracellular Mg2+. 4. Kir6.2/SUR1 currents were less sensitive to 3 mM Na-azide in the presence of MgATP. This apparent reduction in sensitivity is caused by a small activatory effect of Na-azide conferred by SUR. 5. We conclude that, in addition to its well-established inhibitory effect on cellular metabolism, which leads to activation of KATP channels in intact cells, intracellular Na-azide has direct effects on the KATP channel. Inhibition is intrinsic to Kir6.2, is mediated by Na+, and is modulated by SUR. There is also a small, ATP-dependent, stimulatory effect of Na-azide mediated by the SUR subunit. The direct effects of 3 mM Na-azide on KATP channels are negligible in comparison to the metabolic activation produced by the same Na-azide concentration.